stampr: Spatial-Temporal Analysis of Moving Polygons in R - Long, Jed; Robertson, Colin; Nelson, Trisalyn (Journal of Statistical Software, Code Snippets, 2018)
The R package stampr implements functions for analyzing movement in mapped polygon data. Methods described in this paper include deriving change events based on spatial relationships, plotting change events, summarizing measures of distance and direction of movement, characterizing changes in polygon shape changes, and characterizing sequences of polygons over time using graphs. Two examples are used to demonstrate the core functionality available in the stampr package.